2018
DOI: 10.18632/oncotarget.24369
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoid submicron particle ameliorates cognitive deficits and decreases amyloid pathology in Alzheimer’s disease mouse model

Abstract: Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder and is triggered via abnormal accumulation of amyloid-β peptide (Aβ). Aggregated Aβ is responsible for disrupting calcium homeostasis, inducing neuroinflammation, and promoting neurodegeneration. In this study, we generated curcuminoid submicron particle (CSP), which reduce the average size to ~60 nm in diameter. CSP had elevated the bioavailability in vivo and better neuroprotective effect against oligomeric Aβ than un-nanosized curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Curcumin was purchased from the National Institute for the Control of Pharmaceutical and Biological products (Beijing, China), dissolved in polyethylene glycol (PEG <10%) and put in 4°C (Tai et al, 2018).…”
Section: Drug Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin was purchased from the National Institute for the Control of Pharmaceutical and Biological products (Beijing, China), dissolved in polyethylene glycol (PEG <10%) and put in 4°C (Tai et al, 2018).…”
Section: Drug Preparationmentioning
confidence: 99%
“…WT C57BL/6 mice in WT group were given no treatment (n = 20 for each group). All experimental protocols were approved by Institutional Animal Care and Use Committee ( Jiao et al, 2016;Tai et al, 2018).…”
Section: Drug Preparationmentioning
confidence: 99%
“…Ng et al, ). Similarly, many studies have found curcumin treatment to reduce amyloid deposition and improve cognitive performance in Alzheimer's disease (AD) animal models (Bassani et al, ; McClure et al, ; Tai et al, ). Animal studies have lent support to the hypothesis that curcumin could improve cognitive functioning and enhance cell proliferation of dentate gyrus in aged animals (Conboy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can upregulate the critical molecule, PI3K/AKT, and the insulin signaling pathway to reduce insulin resistance in APP/PS1 mice (Feng et al, ). In another study, curcumin treatment significantly ameliorated the cognitive function of APP mice by reducing amyloid deposition and astroglosis (Tai et al, ). In summary, curcumin exhibits its protective efficacy through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 96%